Quality of commitment: Japanese daroo as a speech act operator - Rieser, Lukas (Investigationes Linguisticae, 2019)
This paper proposes a compositional analysis of the meaning of Japanese daroo-utterances with declarative and interrogative force, and final rising and falling intonation. Daroo is analyzed in a framework for speech act felicity as an operator lowering the quality threshold for felicitous assertion. The conveyed meanings of conjecture, confirmation, and doubt uses of darooutterances are predicted from modification of the respective speech act types’ felicity conditions by daroo.